2014
DOI: 10.4103/0377-4929.130849
|View full text |Cite
|
Sign up to set email alerts
|

Mutation profiling in gallbladder cancer in Indian population

Abstract: Aim Gallbladder cancer is an aggressive malignancy usually diagnosed at late stage. The molecular genetics of this cancer is heterogeneous and not well established. Mutation profiling of gallbladder cancer was performed through massarray technology with an aim to identify molecular markers involved in the tumor pathogenesis that can be helpful as markers for early diagnosis and targets for therapy. Materials and Methods Forty nine cases of gallbladder cancer were screened through Sequenom Massarray technolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 9 publications
(11 reference statements)
3
21
2
Order By: Relevance
“…Notably, the present study revealed relatively high frequency (22.2%) of PIK3CA mutations in Japanese BTCs, compared with previous reports (15,16,18,23,36,37,(39)(40)(41). In Caucasian BTC, the frequencies of PIK3CA mutation are limited (16,23,36,37).…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Notably, the present study revealed relatively high frequency (22.2%) of PIK3CA mutations in Japanese BTCs, compared with previous reports (15,16,18,23,36,37,(39)(40)(41). In Caucasian BTC, the frequencies of PIK3CA mutation are limited (16,23,36,37).…”
Section: Discussioncontrasting
confidence: 76%
“…Numerous previous studies have performed genetic analyses of BTC (15,16), and identified TP53 mutations in 8.2-35.7% of GBC cases (17,18), and KRAS mutations in 2-20% of GBC cases (18). KRAS mutations were identified in 20-67% of EBDC cases (19,20), and in 28.6-37.0% of AVC cases (21)(22)(23).…”
Section: Introductionmentioning
confidence: 98%
“…Alterations in oncogenes, tumor suppressor genes, microsatellite instability and methylation of gene promoter areas act in synergy with recurrent or chronic mucosal inflammation to induce cancer although exact cause in not known [30]. Gallstones especially chronic one pose most significant risk although other suspected culprits [31] are advance age, female sex, positive family history, cholelithiasis, obesity (BMI > 30), parasitic infestations, chronic bacterial cholangitis especially by Salmonella and Helicobacter [32], porcelain gallbladder, large polyps >10 mm, heavy metals exposure and abnormal pancreaticobiliary duct junction [33] Clinical features are ominous but those harboring clue include persistent right upper quadrant pain, jaundice, nausea and weight loss [8].…”
Section: Discussionmentioning
confidence: 99%
“…The reflux of pancreatic juice into the extrahepatic biliary duct and GB results in bile changes, inducing chronic inflammation and increased cellular proliferation, which leads to epithelial hyperplasia, metaplasia and biliary tract carcinoma. APBDJ-related GBC has a frequency of KRAS mutation of 50-83% [28] of cases, particularly in codon 12, compared with GBC cases unrelated to APBDJ [29,30], where KRAS mutation presents lower frequencies (2-29%) [31][32][33]. Interestingly, KRAS mutations are also observed in 25-31% of gallbladder adenomas compared with dysplasias and carcinomas, where KRAS mutations are rare [34,35].…”
Section: Pathogenesis and Geographical Variations Of Gallbladder Cancermentioning
confidence: 99%